Depression Among HIV-Positive Pregnant Women at Northwest Amhara Referral Hospitals During COVID-19 Pandemic - Abate HK; Mekonnen CK; Ferede YM (Dove Medical Press, 2021)
Hailemichael Kindie Abate, Chilot Kassa Mekonnen, Yohannes Mulu Ferede Department Medical Nursing, University of Gondar, Gondar, EthiopiaCorrespondence: Hailemichael Kindie Abate Email haile206k@gmail.comBackground: Depression is the most common mental health disorder among HIV-positive pregnant mothers, which increases mortality, poor quality of life; it also increases the burden of disease. Depression hurts birth outcomes and maternal health.Objective: To assess depression and its associated factors among HIV-positive pregnant women attending antenatal care at Northwest Amhara referral hospitals, 2021.Methods: An institution-based cross-sectional study was conducted among 291 HIV-positive pregnant mothers from March 15, 2021 to April 30, 2021 at Northwest Amhara referral hospitals. Census was applied to reach the study participants. An interviewer-administered questionnaire was used for data collection. A binary logistic regression was conducted to see the relationship between dependent variables and independent. Those variables having a p-value of ≤ 0.05 were found to be statistically associated with the response.Results: Depression among HIV-positive pregnant women was found to be 28.7% [95% CI (24.8- 33.40)] with a response rate of 96.04. Age ≥ 30 years [AOR = 1.32, 95% CI (1.24- 3.35)], urban residency [AOR = 1.76, 95% CI (1.57- 4.61)], having first pregnancy < 18 years [AOR = 3.82, 95% CI (1.54- 17.34)], known HIV serostatus during pregnancy [AOR = 1.29, 95% CI (1.08- 2.47)], and COVID-19-related knowledge [AOR = 0.32, 95% CI (0.12- 1.12) were significantly associated with depression.Conclusions and Recommendations: Nearly one-third of the pregnant women attending antenatal care were depressed. The age of the mother, residence, known HIV serostatus during pregnancy, age in the first pregnancy, and COVID-19-related knowledge were significantly associated with depression, and strengthening the existing care provided was the recalled interventions to combat antenatal depression during the COVID-19 pandemic.Keywords: COVID-19, depression, prevalence, HIV positive mothers, pregnancy, referral hospitals, Ethiopia